A COMPARATIVE ANALYSIS OF EPISTEMIC SUBJECTIVE MODAL EXPRESSIONS IN RADIO INTERVIEW DISCOURSE - Situ Jingcheng (International Journal of Literature and Language Studies, 2024)
This article examines epistemic subjective modal expressions in radio interview discourse. The study focuses on the linguistic means by which speakers express their attitudes toward the truth, reliability, and probability of information. The theoretical section discusses the nature of epistemic modality, its relationship with subjectivity, and its pragmatic role in interview communication. The analytical section classifies examples selected from Russian, German, and English radio interviews into four semantic categories: probability, supposition, certainty, and doubt. The findings show that epistemic modal expressions help speakers soften claims, convey personal evaluation, indicate limited knowledge, strengthen credibility, and maintain a natural conversational tone.